Categorical Perception of Facial Emotions in Infancy. (2nd December 2018) - White, Hannah; Chroust, Alyson; Heck, Alison; Jubran, Rachel; Galati, Ashley; Bhatt, Ramesh S.
Abstract : Categorical perception, indicated by superior discrimination between stimuli that cross categorical boundaries than between stimuli within a category, is an efficient manner of classification. The current study examined the development of categorical perception of emotional stimuli in infancy. We used morphed facial images to investigate whether infants find contrasts between emotional facial images that cross categorical boundaries to be more salient than those that do not, while matching the degree of differences in the two contrasts. Five‐month‐olds exhibited sensitivity to the categorical boundary between sadness and disgust, between happiness and surprise, as well as between sadness and anger but not between anger and disgust. Even 9‐month‐olds failed to exhibit evidence of a definitive category boundary between anger and disgust. These findings indicate the presence of discrete boundaries between some, but not all, of the basic emotions early in life. Implications of these findings for the major theories of emotion representation are discussed.